Pengaruh Variasi Pakan Bekatul Suplementasi Daun Pepaya (Carica papaya L.) terhadap Berat Badan dan Karakteristik Ukuran Tubuh Ayam (Gallus domesticus) - Cindyana Putri Puspita Hapsari; Baskoro Adi Prayitno; Meti Indrowati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study evaluated the impact of papaya leaf (Carica papaya L.) supplementation in bran feed on body weight and body size of chickens (Gallus domesticus). Three groups of chickens were fed with papaya leaf flour supplementation to see the efficiency on chicken growth. This study was conducted for 28 days at the